Antibiotic profiling of Clostridium difficile ribotype 176 – A multidrug resistant relative to C. difficile ribotype 027. (December 2015) - Krutova, Marcela; Matejkova, Jana; Tkadlec, Jan; Nyc, Otakar
Abstract: Antibiotic profiling of twenty Czech Clostridium difficile PCR-ribotype 176 isolates revealed a high level of resistance to erythromycin, ciprofloxacin and moxifloxacin (n = 20) and to rifampicin (n = 13). Accumulation of resistance mechanisms to multiple antibiotics highlight that PCR-ribotype 176 belong to problematic epidemic strains. Highlights: Antibiotic susceptibility of Czech Clostridium difficile RT176 was examined. A high level of resistance to erythromycin, rifampicin and moxifloxacin was found. Thr82Ile in gyrA and His502Asn together with Arg505Lys in rpoB were identified. Differences in the resistance spectrum among Polish C. difficile RT176 were observed.